Stereoselective Oxidative Mannich Reaction of Ketones with Dihydrodibenzo‐Oxazepines via a Merger of Photoredox‐/Electro‐Catalysis with Organocatalysis. Issue 12 (29th April 2022) - Hussain, Yaseen; Sharma, Deepak; Kotwal, Namrata; Kumar, Indresh; Chauhan, Pankaj
Abstract: An enantio‐ and diastereoselective sp 3 ‐sp 3 coupling of acyclic/cyclic ketones with dihydrodibenzo‐oxazepines has been developed by merging visible light photo‐redox‐ or electro‐catalysis with organocatalysis. This approach parallelly utilizes Eosin Y or graphite electrodes for the co‐catalyst‐free oxidative conversion of dihydrodibenzo‐oxazepines to oxazepines, followed by L‐Proline catalyzed direct Mannich‐type reaction with ketones. A series of enantioenriched dihydrodibenzo‐oxazepines have been prepared in high yields and enantioselectivity. This method shows substantial advantages over the existing protocols by using potentially safer starting materials and cheap commercially available catalysts. Abstract : Goodbye Tear Gas : The merger of Proline catalysis with organic photoredox catalysis or electrocatalysis provides an alternative strategy for synthesizing enantioenriched dihydrodibenzo[ b, f ][1, 4]oxazepine derivatives by eliminating the direct use of toxic CR gas. Good yields and excellent stereoselectivities have been achieved under mild reaction conditions involving abundant and green sources.